1994
DOI: 10.1093/infdis/169.6.1401
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Shock Mannoproteins as Targets of Secretory IgA in Candida albicans

Abstract: The expression of Candida albicans antigenic determinants reacting with secretory IgA from patients with oral and vaginal candidiasis was investigated under different in vitro conditions. Reversible antigenic transitions were inducible in synthetic medium by temperature shifts, as the yeast cells were positive by an indirect immunofluorescence assay after being incubated at 37 degrees C but not at 25 degrees C. In vitro temperature-inducible C. albicans antigenic determinants reactive with secretory IgA were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…This reactivity was expected, since the mice from whom the splenocytes were obtained were immunized with one of the cell wall stress mannoproteins that have been found to be major targets for salivary sIgA (29). Heat shock proteins are highly conserved and have been shown to be among the dominant antigens recognized in immune responses to a broad spectrum of pathogens (41), including C. albicans and other fungi (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reactivity was expected, since the mice from whom the splenocytes were obtained were immunized with one of the cell wall stress mannoproteins that have been found to be major targets for salivary sIgA (29). Heat shock proteins are highly conserved and have been shown to be among the dominant antigens recognized in immune responses to a broad spectrum of pathogens (41), including C. albicans and other fungi (22).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have demonstrated that salivary sIgA reacts with a group of stress mannoproteins located on the cell wall surface-mannoproteins whose expression is modulated by a number of factors, including the temperature of growth, composition of growth medium, yeast-mycelium transition, and pH (3,29,31,39). We have also demonstrated that salivary sIgA inhibits the adhesion of C. albicans to plastic and composite restorative dental materials and that the inhibitory effect can be mimicked by MAbs directed against cell wall antigens of C. albicans (24,36).…”
mentioning
confidence: 99%
“…They were produced following standard methods in BALB/c mice immunized by subcutaneous injections of a partly purified antigen of 260 kDa from germ tubes (PA lOF) and a partly purified heat shock mannoprotein of 200 kDa from a blastoconidium extract (C6) as previously described (Ponton et al, 1993;Polonelli et al, 1994). Antibodies used in this study were contained in ascites fluid from mice injected with the hybridomas.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Our group has been working during the past few years on the development of monoclonal antibodies against C. albicans antigenic determinants, also including C. albicans heat shock mannoproteins (Ponton et al, 1993;Polonelli et al, 1994). We have tested a panel of these antibodies on human ovarian carcinoma tissue, and two of them showed promising initial results in a small preliminary study.…”
mentioning
confidence: 99%
“…Monoclonal antibody (MAb) C7 was raised against a protein epitope of a stress mannoprotein of Ͼ200 kDa that is the main target of salivary secretory immunoglobulin A (IgA) in the cell wall of Candida albicans (7). This MAb exhibits potent fungicidal activity against C. albicans, Candida lusitaniae, Cryptococcus neoformans, Aspergillus fumigatus, and Scedosporium prolificans (5), and it has been shown to protect mice from invasive candidiasis (10).…”
mentioning
confidence: 99%